Advanced flower-like Co3O4 with ultrathin nanosheets and 3D rGO aerogels as double ion-buffering reservoirs for asymmetric supercapacitors. (1st May 2018) - Lai, Changwei; Sun, Ying; Zhang, Xueqin; Yang, Hong; Kang, Weiwei; Lin, Baoping
Abstract: An advanced flower-like DBS-Co3 O4 hierarchical microspheres with specific surface as electrochemical active sites have been synthesized from a novel DBS-intercalated Co(OH)2 (DBS-Co(OH)2 ) flower spheres with atomically ultrathin Co(OH)2 nanosheets. The hierarchical DBS-Co3 O4 flower microspheres exhibit specific capacitance value of 1104.4 F g -1  at a current density of 0.5 A g −1 in 6 M KOH solution. Meanwhile, the 3D rGO aerogels are prepared by a facile method as negative electrode materials, and the specific capacitance of 213.3 F g −1 can be achieved at a current density of 2 A g −1 . Therefore, both the DBS-Co3 O4 microspheres with opened hierarchical honeycomb-like structures and 3D rGO aerogels with an interconnected pore network structures can be filled with electrolyte ions as double "ion-buffering reservoirs" in the charge-discharge process. Hence, the asymmetric supercapacitors of the double "ion-buffering reservoirs" are fabricated with the DBS-Co3 O4 as positive electrode of promising Faradaic pseudocapacitors materials and the 3D rGO aerogels as the negative electrode of electrical double-layer capacitors materials, exhibiting a high energy density of 25.5 Wh kg −1 at the power density of 400 kW kg −1 with excellent cycling performance. Graphical abstract: The asymmetric supercapacitors of the double "ion-buffering reservoirs" are fabricated with the 3D flower-like DBS-Co3 O4 microspheres as positive electrode materials and 3D-rGO aerogels as negative electrode materials with excellent electrochemical performance for energy storage application.